Design de embalagem: desenvolvimento de embalagens de ovos para a empresa Tapuio Agropecuária Ltda - Araújo, Tiago de Sousa (2015)
This paper aims to create an egg packaging family for the Brazilian company Tapuio Agropecuária LTDA, currently with the brand names of Mr. Caipira, Mr. Ômega 3 and Mr. Ovo Saúde [Mr. Free-range, Mr. Omega 3, Mr. Healthy egg]. Therefore, grounding data about packaging design for retail was researched. It comprehends, as main methodology, the studies of Fábio Mestriner (2002) which covers strategies and key points focused on the techniques in Inteligência de Embalagem™ in order to identify the needs of the market niche desired to achieve. The data analysis and the information courtesy of the company allowed the construction of a briefing and requirements that served as a base for the creation of design proposals. Lastly, through feedback from the companies involved, it was decided which structural and graphic proposals are going to the market and then prototypes were produced to simulate the final proposal at the point of sale.